2020
DOI: 10.1016/j.stemcr.2020.02.011
|View full text |Cite
|
Sign up to set email alerts
|

Divergent Effects of Dnmt3a and Tet2 Mutations on Hematopoietic Progenitor Cell Fitness

Abstract: The DNA methylation regulators DNMT3A and TET2 are recurrently mutated in hematological disorders. Despite possessing antagonistic biochemical activities, loss-of-function murine models show overlapping phenotypes in terms of increased hematopoietic stem cell (HSC) fitness. Here, we directly compared the effects of these mutations on hematopoietic progenitor function and disease initiation. In contrast to Dnmt3a-null HSCs, which possess limitless self-renewal in vivo, Tet2-null HSCs unexpectedly exhaust at the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
52
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(56 citation statements)
references
References 34 publications
4
52
0
Order By: Relevance
“…Mutations in TET2 are nonsense or missense changes that lead to a loss of function [ 122 ] and DNA hypermethylation due to decreased production of 5-hmC. Mutant TET2 increases the expression of HSC self-renewal genes and sensitizes hematopoietic cells to acquire other mutations and leads to significant myeloid lineage skewing [ 123 ] and increased IL-6 production [ 124 ]. The order of mutation acquisition can influence the MPN phenotype; mutations in TET2 arising prior to JAK2 V617F favors the ET phenotype, but the acquisition of JAK2 V617F in a TET2 non-mutated background is more likely to result in the PV phenotype [ 125 ].…”
Section: Disease Modifiersmentioning
confidence: 99%
See 1 more Smart Citation
“…Mutations in TET2 are nonsense or missense changes that lead to a loss of function [ 122 ] and DNA hypermethylation due to decreased production of 5-hmC. Mutant TET2 increases the expression of HSC self-renewal genes and sensitizes hematopoietic cells to acquire other mutations and leads to significant myeloid lineage skewing [ 123 ] and increased IL-6 production [ 124 ]. The order of mutation acquisition can influence the MPN phenotype; mutations in TET2 arising prior to JAK2 V617F favors the ET phenotype, but the acquisition of JAK2 V617F in a TET2 non-mutated background is more likely to result in the PV phenotype [ 125 ].…”
Section: Disease Modifiersmentioning
confidence: 99%
“…U2AF1 recognizes pyrimidine-rich tracts with a conserved terminal AG in 3 ′ splice sites [ 145 ]. The most prevalent somatic mutations affect Q157 and its surroundings; p.Q157 mutants generate mis-splicing of ARID2 and EZH2 [ 123 ] and are associated with a worse outcome [ 146 ]. Patients can also harbor mutations in serine 34 (p.S34F/Y) that cause different expression and splicing patterns than p.Q157 mutations and have been associated with increased splicing, accumulation of R loops and exon skipping [ 142 , 147 ].…”
Section: Disease Modifiersmentioning
confidence: 99%
“…Loss of normal TET2 function decreases 5hmC production, leading to DNA hypermethylation. This has a particular effect on HSCs increasing expression of self-renewal gene signatures, sensitizing haematopoietic cells to cooperating mutations and skewing towards myelomonocytic differentiation, [121] and sensitises haematopoietic cells to cooperation mutations. TET2 loss of function and subsequent hypermethylation patterns favour myelomonocytic lineage in HSC priming.…”
Section: Tet2 (Ten-eleven Translocation 2)mentioning
confidence: 99%
“…Recent study using a mammalian two-hybrid screen has revealed that SMAD nuclear interacting protein 1 (SNIP1) recruits TET2 to the promoters of c-MYC target genes, including those involved in DNA damage response and cell viability, thereby connecting epigenetic control to maintenance of genome stability. 52 Ostrander et al 53 and Tal1, to CpG-rich erythroid motifs, which then induces block of erythroid differentiation and skewed differentiation to myelomonocytic lineage in Tet2-null HSCs ( Figure 5). 55 Together, these data suggest that Tet2 loss-mediated disruption of DNA methylation in gene promoters as well as in TF binding sites alters the landscape of hematopoietic differentiation and promotes hematopoietic transformation.…”
Section: Targ E Ts Of Te T2-med Iated C Y Tos Ine Mod Ifi C Ati On mentioning
confidence: 99%
“…Ostrander et al 53 compared functional difference between Dnmt3a ‐null and Tet2 ‐null HSPCs and found that Tet2 loss induced profound myeloid lineage skewing, whereas Dnmt3a loss conferred limitless self‐renewal to HSCs. RNA sequencing (RNA‐seq) and assay for transposase‐accessible chromatin‐sequencing (ATAC‐seq) deciphered divergent transcriptomes and chromatin accessibility underlying these functional differences 53 . Genome‐wide mapping of TET2 binding sites through ChIP and sequencing, together with ATAC‐seq and RNA‐seq, uncovered that TET2 localizes to regions of open chromatin and cell type‐specific enhancers 54 .…”
Section: Targets Of Tet2‐mediated Cytosine Modification and Its Functmentioning
confidence: 99%